2014
DOI: 10.4251/wjgo.v6.i9.344
|View full text |Cite
|
Sign up to set email alerts
|

Tricks and tips in pancreatoduodenectomy

Abstract: Author contributions: Pallisera A wrote the introduction and the section on the artery-first approach; Ramia JM wrote the section on arterial complications during pancreatoduodenectomy; Morales R wrote the section on extended lymphadenectomy for pancreatic head adenocarcinoma. AbstractPancreaticoduodenectomy (PD) is the standard surgical treatment for tumors of the pancreatic head, proximal bile duct, duodenum and ampulla, and represents the only hope of cure in cases of malignancy. Since its initial descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…For instance, most of the blood supply to the extrahepatic biliary tree comes from the RHA or rRHA. Accidental injury to these arteries during hepatic surgery might lead to ischaemia of the biliary anastomosis. Ishigami and colleagues reported that variant hepatic artery anatomy in a liver transplant recipient increased the risk of hepatic artery complications after transplantation by 18 per cent.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, most of the blood supply to the extrahepatic biliary tree comes from the RHA or rRHA. Accidental injury to these arteries during hepatic surgery might lead to ischaemia of the biliary anastomosis. Ishigami and colleagues reported that variant hepatic artery anatomy in a liver transplant recipient increased the risk of hepatic artery complications after transplantation by 18 per cent.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding liver arterial supply, it is described as ‘normal anatomy’ when the CHA originates the PHA after the emergence of the GDA; next, the PHA separates into right and left hepatic arteries within the hepatoduodenal ligament. The knowledge of hepatic artery supply is essential to avoid iatrogenic complications during HPB surgery; in the presence of anatomical variations accidental ligation, provoking hepatic necrosis, ischemic biliary injury and anastomotic fistula can complicate the peri- and postoperative course ( 14 ). With the grooving number of liver transplantation, the importance of the hepatic artery anatomy become crucial and many authors proposed classifications describing liver vascular variations based on their studies ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the grooving number of liver transplantation, the importance of the hepatic artery anatomy become crucial and many authors proposed classifications describing liver vascular variations based on their studies ( 7 ). The most often described hepatic artery anatomical variations are: i) An anomalous RHA from the SMA (10–21%); ii) displaced LHA from the LGA (4–10%); iii) displaced RHA and LHA; iv) an accessory RHA and/or LHA (1–8%); v) displaced CHA from SMA or aorta (0,4-4,5%); or vi) quadrifurcation of hepatic artery ( 14 ). In our study we described two independent cases of hepatic arterial anatomic variants where a HAS arised directly from SMA and traveling posterior to the pancreatic head and vena porta.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations